Blockade of Pachytene piRNA Biogenesis Reveals a Novel Requirement for Maintaining Post-Meiotic Germline Genome Integrity - Zheng, Ke (Public Library of Science, 2012)
Piwi-interacting RNAs are a diverse class of small non-coding RNAs implicated in the silencing of transposable elements and the safeguarding of genome integrity. In mammals, male germ cells express two genetically and developmentally distinct populations of piRNAs at the pre-pachytene and pachytene stages of meiosis, respectively. Pre-pachytene piRNAs are mostly derived from retrotransposons and required for their silencing. In contrast, pachytene piRNAs originate from ∼3,000 genomic clusters, and their biogenesis and function remain enigmatic. Here, we report that conditional inactivation of the putative RNA helicase MOV10L1 in mouse spermatocytes produces a specific loss of pachytene piRNAs, significant accumulation of pachytene piRNA precursor transcripts, and unusual polar conglomeration of Piwi proteins with mitochondria. Pachytene piRNA–deficient spermatocytes progress through meiosis without derepression of LINE1 retrotransposons, but become arrested at the post-meiotic round spermatid stage with massive DNA damage. Our results demonstrate that MOV10L1 acts upstream of Piwi proteins in the primary processing of pachytene piRNAs and suggest that, distinct from pre-pachytene piRNAs, pachytene piRNAs fulfill a unique function in maintaining post-meiotic genome integrity.